A SURVEY STUDY ABOUT AWARENESS OF MENSTRUAL HYGIENE IN AGE GROUP OF 12-19 YEARS FEMALES IN RURAL VADODARA - Jain Tulika; Khan Jolly N; Makwana Payal V; Pipaliya Satyavati G; Ambaliya Meera P; Gohil Rachana T; Bavadiya Urvish D; Bhaiya Gunjan P (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background:Menstrual hygiene and management (MHM) are an important aspect of a woman's reproductive life. But there is little awareness about the physiological process and maintenance of hygiene in young females. Also, many taboos in respect to this are prevalent especially in the rural areas.Objectives:This paper seeks to identify the various practices and challenges that females of the age group of 12- 19, face in terms of menstrual hygiene in the rural area in Vadodara district in Gujarat.Materials and Methods:A survey was conducted in various villages of Western Vadodara to determine the level of awareness about menstruation, its hygiene and management from March 2022 to August 2022. 795 girls of age group 12-19 were covered during the survey. Data were collected by the predesigned questionnaires survey form.Result:It was found that 65.3% girls i.e., every six out of the ten used sanitary pad and 13.8% girls uses cotton cloth. However, it was also found that 20.4% uses both cotton cloths and pad. while approximately 0.5% of girls used other materials which they didn’t reveal exactly. When enquired more, it was also found that girls who used sanitary pad had little knowledge about its disposal.Conclusion: After doing survey it was concluded that with education and awareness through various mediums, the majority of girls have adopted the use of sanitary napkins. But There is a serious need to create awareness about method of disposal of sanitary materials.